1982
DOI: 10.1017/s0021859600030033
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic and phenotypic parameters of some weight and fleece traits in a coarse-wool breed of sheep

Abstract: SUMMARYA study using 1150 lambs to estimate genetic and phenotypic parameters of some weight and fleece traits was carried out on coarse-wool Barki sheep. The weight traits were birth, weaning, yearling weights and daily gains whereas fleece traits included kemp score, staple length and greasy-fleece weight.Heritability estimates of weight traits were within the range 0·25–0·30. Those of fleece traits were 0·16, 0·21 and 0·43. The repeatability estimates of fleece traits were 0·18, 0·38 and 0·53 for staple len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
2
6
0
Order By: Relevance
“…This might be due to differences in nutrition level as a result of differences in rainfall and vegetation. These results were in agreement with those obtained by Guirgis et al, (1982) on Barki, Lewer et al, (1983) on Perendale ewes and Magid and Zaied (1992) on Barbary sheep. On the other hand, Aboul-Naga (1970), working on Merino, Ossimi and Barki sheep, found that differences in staple length due to year effect were not significant.…”
Section: Coat Depthsupporting
confidence: 93%
See 3 more Smart Citations
“…This might be due to differences in nutrition level as a result of differences in rainfall and vegetation. These results were in agreement with those obtained by Guirgis et al, (1982) on Barki, Lewer et al, (1983) on Perendale ewes and Magid and Zaied (1992) on Barbary sheep. On the other hand, Aboul-Naga (1970), working on Merino, Ossimi and Barki sheep, found that differences in staple length due to year effect were not significant.…”
Section: Coat Depthsupporting
confidence: 93%
“…The high heritability of belly wool and fleece Kemp score in Barki lead to conclude that any improvement in belly wool cover will be obtained by genetic as well as environmental improvement on the basis of highly significant effect of year, sex and age on belly wool cover. The present of h 2 was close to that reported by Guirgis et al (1982), in Barki sheep as 0.43. In the same trend El-Gabbas (1993) reported that the genetic factors might have a major role in controlling Kemp score to give importance for selection programs as indicated by highly significant animal effect.…”
Section: Heritability Estimatessupporting
confidence: 90%
See 2 more Smart Citations
“…Kemp score was lower (P<0.05) in G3 (1.55± 0.238) than in G1 (2.36 ± 0.238) while Kemp score of G2 (1.77 ± 0.238) did not differ than those of G1 or G3. The lower Kemp score is more desirable trait as particularly when companied with higher fleece opening (Guirgis et al, 1982). Wool characteristics: Mean fiber diameter (MFD) was thinner (P<0.05) in G2 (32.18 ± 2.067 µm) and G3 (29.68 ± 2.067 µm) than in unshorn G1 (36.74 ± 2.067 µm) but the difference between G2 and G3 was not significant (Table 4).…”
Section: Coat Characteristicsmentioning
confidence: 96%